NFC and 2FA: the death of the password?. (July 2015) - Watts, Steve
Abstract : Since the dawn of the digital age, we've signed up to the password, trusting in its ability to keep our digital lives safe from thieves and those who would mean us harm. Moore's law tells us that every two years computing power doubles – meaning every two years the amount of time it takes to crack a password using a brute force attack halves. It's now reached the point where a password can be cracked in minutes, sometimes in as little as just six seconds. Six seconds to potentially lose your entire digital life.